Perception as Mediator between Knowledge and Attitude of Community about COVID-19 in Dentistry - Gunardi, Indrayadi; Amtha, Rahmi; Widyadhana, Helena G. V. (e-GiGi, 2022)
Abstract: The main transmission medium of Covid-19 is aerosol from nose and oral cavity when coughing, sneezing, and speaking. Due to the vast transmission of the virus, the Indonesian government has established various health protocols to reduce the impact of the disease. Until now, the high number of confirmed COVID-19 patients in Jakarta is suspected as a result of lack of knowledge and perception. This study was aimed to determine the relationship between knowledge, perception, and attitudes of COVID-19 transmission in dentistry in JABODETABEK Jakarta. This was an analytical and observational study with a cross-sectional design using online questionnaire containing 50 questions. This study was conducted on 572 subjects. The validity of the questionnaire was analyzed by using the Rasch model and the linear regression between variables and mediation analysis. The results obtained that the questionnaire showed a Cronbach alpha of 0.82 and item reliability of 1.00 with a separation of 29.97. Most subjects were in high category of knowledge (97.20%), perception (60.66%), and attitudes (93.88%). There was a relationship between knowledge and perception (p<0.001; 95%CI 0.357-0.925); perception and attitude (p<0.001; 95%CI 0.643-0.829); and the perception as a mediator between both variables. In conclusion, JABODETABEK community’s perception of COVID-19 transmission has an impact as mediator or influence people’s attitude in implementing their knowledge in dentistry.Keywords: knowledge; perception; attitude; COVID-19 Abstrak: SARS-CoV-2 merupakan tipe coronavirus baru yang dapat menimbulkan penyakit COVID-19. Media transmisi primer dari virus ini ialah aerosol yang keluar dari hidung dan rongga mulut saat batuk, bersin, maupun bicara. Oleh karena transmisi tinggi virus, pemerintah Indonesia telah menetapkan berbagai protokol kesehatan untuk menurunkan dampak dari keparahan penyakit. Hingga sekarang, adanya sejumlah tinggi kasus COVID-19 pada populasi Jakarta, diduga akibat adanya pengetahuan dan persepsi yang rendah. Penelitian ini bertujuan untuk menentukan hubungan antara pengetahuan, persepsi, dan sikap dari transmisi COVID-19 dalam bidang kedokteran gigi pada populasi JABODETABEK. Jenis penelitian ialah observasional analitik dengan desain potong lintang, dilakukan dengan kuesioner online yang terdiri dari 50 pertanyaan, dan diujikan pada 572 responden. Validitas kuesioner dianalisis model Rasch, dan regresi linier antara variabel dan analisis mediasi. Hasil penelitian mendapatkan kuesioner menunjukkan Cronbach alpha 0,82 dan reliabilitas item 1 separasi 29,97. Seluruh responden masuk ke dalam kategori pengetahuan tinggi (97,20%), persepsi (60,66%) dan sikap (93,88%). Hubungan ditemukan antara pengetahuan dan persepsi (p=<0,001; 0,357-0,925), persepsi dan sikap (p=<0,001; 0,643-0,829), dan persepsi sebagai mediator antara kedua variabel. Simpulan penelitian ini ialah persepsi masyarakat JABODETABEK terhadap transmisi COVID-19, berperan sebagai mediator atau memengaruhi sikap mereka dalam mengimplementasikan pengetahuannya di bidang kedokteran gigi.Kata kunci: pengetahuan; persepsi; sikap; COVID-19